The Holocaust : the origins, events, and remarkable tales of survival - Steele, Philip, 1948- (Scholastic Inc., 2016)
Explores the history behind what led to the Holocaust, discussing the realities of life in the concentrations camps and includes eyewitness accounts of courage and survival.